Pengaruh TO-BE pada Perancangan Sistem Informasi - Riva Fani; Chris Jhon Simanungkalit; Muhamad Shandy; Naufal Naufal; Muhamad Alfryan; Ikhsan Ikhsan; Arimbi Arimbi; Carlos Carlos; Oktaviana Bangun; Tafaawo Larosa (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
Effective information system design requires a clear and comprehensive understanding of the desired ideal system conditions in order to support organizational objectives. The TO-BE approach is a business process modeling method that describes future system conditions as a conceptual and strategic basis for improving existing AS-IS conditions. This study aims to analyze the effect of implementing the TO-BE approach in information system design on the clarity of system requirements, overall process efficiency, and the quality of system design outcomes. The research method used is descriptive-analytical research with a qualitative approach, employing data collection techniques such as literature review, direct observation, and in-depth analysis of system design documents. The results show that implementing the TO-BE approach in information system design provides a more structured and systematic overview of business processes, minimizes mismatches between system functionality and user needs, and improves the effectiveness and efficiency of business processes. Furthermore, the TO-BE approach assists system developers and analysts in designing system solutions that are aligned with organizational goals, operational requirements, and user expectations. Thus, implementing the TO-BE approach positively impacts the overall quality of information system design and is recommended as a critical and essential step in information system development initiatives.